Analysis of The Structural Form of Silek Dance & Values in The Traditional Malay Wedding Procession in Kampar Regency - Ria Muliani; Agusti Efi (Jurnal Adat dan Budaya Indonesia, 2026)
This study rested on the structural performance and cultural values in Silek Dance in traditional Malay wedding ceremony in Kampar Regency. A synergetic relationship of dance and socio-cultural aspects is observed in interviews with dancers, a traditional leader, and a local community through a descriptive qualitative method. The result sReveal a structured Silek Dance performance with an opening, a middle and a closing part that is passed down from generation to generation. Each phase symbolizes a function in the ceremonious aspects of its context, from paying respect and social cohesion to recovering balance at the end of the ritual. It is also a dance that shares deep core cultural values of politeness, harmony, restraint, and social balance. The result is indicative of the fact that Silek Dance is not only a traditional art performance but also a medium of culture which maintains the values and Kampar Malay identity in the era of modernization.